THE MULTILEVEL EDUCATIONAL COMPLEX AS A FACTOR IN THE STABILIZATION OF THE LABOR MARKET AND STRUCTURAL BALANCE - Aleksandr S. Senin; Elena A. Bubenok (Модернизация, инновация, развитие)
This article describes one of the problems of the national economic complex – the problem of the labor market in Russia competent experts. The article provides statistical data describing the level of wages in the sphere of education and medicine. The problems of the labor market and educational complex, recommendations to change the situation in these areas. The presented article shows that the development of the national innovation system in the framework of sustainable development requires consistent evolutionary change of priorities in the areas of research, development, testing and implementation of all types of innovation, including in the development of the educational sector. The purpose of work is to analyze the interaction of the paradoxes of the educational sector and the labor market, the study of occurrence in this connection of new scientifi c problems, considering the prevailing laws and assessing their impact on the current state of the labor market. Methodology. Such analysis techniques were used to complete this article as legal, comparative, Economics and Statistics. Conclusions / relevance. The practical signifi cance of this work lies in the fact that in the article the necessity of adapting education to the needs of modern society. This process causes the search for science-based assessments of the quality of higher education and oversee its development processes. The most important condition for improving the quality of higher education are systematic monitoring and analysis of objective data about the quality of training and preparedness of students.